Chemical nonequilibrium modelling of a free-burning nitrogen arc. (9th October 2020) - Wang, Hai-Xing; Zhu, Tao; Sun, Su-Rong; Liu, Gang; Murphy, Anthony B
Abstract: Thermal and chemical nonequilibrium modelling is performed to investigate the plasma characteristics of a nitrogen arc. The arc plasma is coupled with the electrodes self-consistently in the computational domain. The self-consistent effective binary diffusion coefficient approximation treatment of diffusion and a generalized form of Ohm's law are incorporated in the model. It is found the electric field has to undergo a reversal in front of the anode to preserve current conservation due to the strong diffusion current density. No field reversal is found in front of the cathode. The detailed chemical reaction processes are analyzed to understand the species density behaviour. Along the cathode surface, the maximum values of current density and heat flux density occur at the intersection of the flat tip and the conical surface. The distributions of different components of the current density and heat flux density change with the arc current. On the anode side, the electric field and diffusion components contribute to the current density, and have opposite signs and similar magnitudes on the axis, leading to an off-axis maximum of the current density. The electron condensation heat makes the largest contribution to the total heat flux in the high current density region, and the heavy-species contribution from the plasma becomes important in the arc fringe. The high heat flux and current density at the anode show that the nitrogen arc possesses excellent energy source properties for arc welding and other processes that require workpiece melting.